Vibration control of civil engineering structures using magneto-rheological dampers - Braz-César, Manuel (2012)
This paper addresses the semi-active contro l of a scaled model frame equipped with a magneto-rheological (MR) damper, deve loped within the COVICOCEPAD project (Eurocores program S3T) reporting related research and development related with structural control of civil engineering structures. The scaled frame is a model of a three-storey building with a single MR damper rigidly connected between the ground and the first floor. Among the vari ety of semi-active control algorithms available for MR damper control, a cli pped-optimal control algorithm model-based on the linear quadratic regul ator (LQR) and a fuzzy control non-model-based algorithm were selected as the semi-activ e controllers. A small sponge type MR damper was experimentally tested under seve ral input excitations to characterize the damper performance. The simple Bouc-Wen phenomenological model was chosen to simulate the nonlinear behavior of the MR damper and the related model parameters were obtained based on the ex perimentally measured responses. Some numerical results of the uncontrolled and controlled frame under El Centro earthquake are given to evaluate the perfor mance of the selected control strategies.